2016
DOI: 10.1088/2053-1583/3/2/025011
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phosphorene in air: understanding at atomic level

Abstract: Phosphorene is a promising two dimensional (2D) material with a direct band gap, high carrier mobility, and anisotropic electronic properties. Phosphorene-based electronic devices, however, are found to degrade upon exposure to air. In this paper, we provide an atomic level understanding of stability of phosphorene in terms of its interaction with O 2 and H 2 O. The results based on density functional theory together with first principles molecular dynamics calculations show that O 2 could spontaneously dissoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
269
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(283 citation statements)
references
References 35 publications
13
269
1
Order By: Relevance
“…Significantly, the exothermic energies Q corresponding to the O 2 dissociation on phosphorene and antimonene are −4.15 and −1.01 eV/O 2 , respectively. Note that the triplet state of O 2 is used to calculate the dissociation energy, and the method has been well confirmed in phosphorene oxidation31. Such smaller exothermic energies strongly support that O 2 are more likely to react with phosphorene than antimonene, evidencing higher air stability of antimonene.…”
Section: Resultsmentioning
confidence: 77%
“…Significantly, the exothermic energies Q corresponding to the O 2 dissociation on phosphorene and antimonene are −4.15 and −1.01 eV/O 2 , respectively. Note that the triplet state of O 2 is used to calculate the dissociation energy, and the method has been well confirmed in phosphorene oxidation31. Such smaller exothermic energies strongly support that O 2 are more likely to react with phosphorene than antimonene, evidencing higher air stability of antimonene.…”
Section: Resultsmentioning
confidence: 77%
“…It is theoretically predicted that the exposure of up to 3-5 layers thick BP to ambient light and molecular oxygen leads to the generation of superoxide radicals (where the reaction proceeds at −4.11 eV with respect to the vacuum level), which is further expedited in the presence of H 2 O. 13,[30][31][32][33][34] The generated superoxide radicals are proposed to interact with the BP surface to produce P x O y , resulting in the eventual loss of pristine BP. 10,13 The process of superoxide radical formation cannot be sustained in BP that is beyond 3-5 layers in thickness due to the changes in the band positions in thicker BP flakes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, using a few layers of phosphorene, researchers have successfully fabricated the field-effect transistor67, which is a desirable device for biodetection and biosensing8910. Simulation and experimental results showed that phosphorene in water is more stable than that in air1112. The good stability of phosphorene in water creates the chances for phosphorene’s applications in biological fields.…”
mentioning
confidence: 99%